1991
DOI: 10.1111/j.1538-4632.1991.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Mapping and Identifying Small Clusters of Rare Diseases with Applications to Geographical Epidemiology

Abstract: Geographical variation operates at a variety of scales. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In agreement with our study, other studies have also reported spatial clustering of HL at diagnosis [42,20,19,21] whereas, evidence from the mentioned, large UK study was weak [15]. A study in New Zealand found no evidence of global clustering of HL at birth [14].…”
Section: Discussion In the Context Of Other Studiessupporting
confidence: 91%
“…In agreement with our study, other studies have also reported spatial clustering of HL at diagnosis [42,20,19,21] whereas, evidence from the mentioned, large UK study was weak [15]. A study in New Zealand found no evidence of global clustering of HL at birth [14].…”
Section: Discussion In the Context Of Other Studiessupporting
confidence: 91%
“…To our knowledge only two studies have corrected for multiple testing . Lastly, though many studies have investigated acute lymphoid leukaemia (ALL) only few studies have examined the spatial distribution of acute myeloid leukaemia (AML) …”
mentioning
confidence: 99%